Inventário das cinzas: Brasas dormentes da produção literária sobre o Cerrado em Goiás - Curado, Bento Alves Araújo Jayme Fleury (2016)
The work entitled Inventory of ashes: Embers dormant literary production of the Cerrado in Goiás discusses minutiae in the formation of a literary ideas about Biome Territory heart of Brazil. It focuses on the search for a cultural identity of goianos people regarding the environment in which they live. Rediscusses different literary styles such as short story, novel, chronic, poem, novels, with the identification of a society focused on itself. Their analysis and the timing thereof satisfied the time. Each author with his work, was analyzed to discuss the Cerrado and its different modalities. The research was literature and documents on primary source for the elucidation of the theme and serve henceforth as a subsidy to teachers both of Geography, as Literature.